2018
DOI: 10.1002/marc.201800271
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐Based Transparent Conductive Film Consisting of Polyethylene Furanoate and Silver Nanowires for Flexible Optoelectronic Devices

Abstract: Exploiting biomass has raised great interest as an alternative to the fossil resources for environmental protection. In this respect, polyethylene furanoate (PEF), one of the bio-based polyesters, thus reveals a great potential to replace the commonly used polyethylene terephthalate (PET) on account of its better mechanical, gas barrier, and thermal properties. Herein, a bio-based, flexible, conductive film is successfully developed by coupling a PEF plastic substrate with silver nanowires (Ag NWs). Besides th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…Lam et al [139] have demonstrated the application potentials of PEF as a replacement for commonly used PET in flexible optoelectronic devices. By coupling PEF plastic substrate with silver nanowires (Ag NWs), a flexible, conductive film was developed.…”
Section: Selected Uses/applicationsmentioning
confidence: 99%
“…Lam et al [139] have demonstrated the application potentials of PEF as a replacement for commonly used PET in flexible optoelectronic devices. By coupling PEF plastic substrate with silver nanowires (Ag NWs), a flexible, conductive film was developed.…”
Section: Selected Uses/applicationsmentioning
confidence: 99%
“…[14] FDCA is an important building block for renewable biodegradable polymers and has been used in the packaging industry [15] to replace PET and also in flexible polymer films for optoelectronics. [16] Aliphatic C-4 diacids such as succinic and malic acid are important platform chemicals and a gateway to several high value intermediates used in the pharmaceutical and chemical industry. Due to the renewable nature and non-toxicity of these compounds they have found use as high-value monomers providing unique functional properties for next generation materials.…”
Section: Synthesis Of Diacid Monomersmentioning
confidence: 99%
“…Despite the interest in FDCA-based polyesters, there is a limited amount of information on the development of furan-based nanocomposites. The existing studies mainly focus on the addition of carbon-based nanofillers and nanoclays in PEF [ 15 , 26 , 27 , 28 , 29 , 30 ], but some research also deals with PBF [ 31 ], poly(propylene furanoate) (PPF) [ 32 , 33 ], or poly(hexamethylene furanoate) (PHF) [ 22 ], mainly prepared by in-situ polymerization in presence of a nanofiller suspension. In these cases, nanofillers are added to increase the mechanical properties but especially the crystallization kinetics and the gas barrier performance [ 22 ].…”
Section: Introductionmentioning
confidence: 99%